Comparison of Measurement Information Technology Services of Organization Case Study : Faculty of Science and Technology PTWIT - Thongkaew, Piyawat; Janthet, Praewphisut; ใจเดช สุจรรยา; Kanchanarat, Kittisak (Journal of Advanced Development in Engineering and Science, 2023)
The objective of this study was to measure the efficiency information technology services of organization: case study of faculty of science and technology, Pathumwan Institute of Technology. This study was to compare performance benchmarking. It focused on the strength and weakness of information technology services by comparing with Benchmarking. The process of this study started from setting the vision and strategy of institute. Then, analyzed the inside and outside circumstance of information technology services organization. Next, set the benchmarking in 4 aspects, servicing, resource, management and personnel following by the process of benchmarking.1.Planning. 2. Data collecting. 3. Analyzed the benchmarking 4.Applied the result from satisfied of wireless information technology services. From the study, Faculty of Science and Technology has not installed and set up a wireless network so it not available for students and staff to used. Now using can be provided them with only the signal from Pathumwan Institute of Technology. However the signal quality is poor. Can be connected to a certain point only.